TINDAK PIDANA PENCURIAN BERDASARKAN PASAL 363 AYAT 1 KE-4 (PUTUSAN NOMOR 50/PID.B/2020/PN.JKT.TIM) - Muhammad Daffa Rianto; Fachri Bey (Fakultas Hukum Universitas Trisakti, 2022)
Research findings on the crime of theft based on Fourth paragraph of Article 363. The current passage hardly complies with the Criminal Code's Article 363 paragraph 1 fifth. At the time of the aforementioned crime, which was committed with the participant's assistance rather than using the forged-based key described in Article 100 of the Criminal Code, law enforcement officials were not aware of modern technology. Because perpetrating a theft necessitates entering a specific location that qualifies for inclusion, i.e., a theft that is carried out by two or more people (Decision No. 50/Pid.B/2020/Pn.Jkt.Tim). The method of statistical analysis used to create scientific work in this case is normative statistical analysis, descriptive statistical analysis, data collection through literature studies, and statistical analysis using a qualitative approach so that the author can conclude that. The judge asserts that the 5th article 363 paragraph (1) is incorrect because.